Dual band active microstrip monopole antenna for wireless local area network - Abdullah Al-Malsi, Abdulrahman (2009)
An active antenna with simultaneous transmit and receive function, integrate an active devices onto a printed antenna to improve its performance or combine functions within the antenna itself. Such antenna are of increasing interest, as system designers require more complex functions to be implemented in reduced space. This thesis discusses the integration of active antennas by combining receive functions into one single antenna. Two main components in the design are passive dual band microstrip monopole antenna and active device (low noise amplifier). All the simulations are done using the CST Microwave Software and Advance Design System (ADS). The terminology of active integrated antenna indicates specifically that the passive antenna elements and the active circuitry are integrated on the same substrate. Two different set of frequencies have been allocated for the WLAN application. One is at 2.4 GHz band and the other at 5.8GHz band. Two different set of frequencies need two different set of antenna. It can be solved by using one antenna for two different systems. Basically the design of transmit or receive passive microstrip monopole antenna the gain is not constant over a desired frequency band. The implementation of amplifier (low noise amplifier) in a passive antenna structure increases the antenna gain and improves the noise performance. The antenna will be designed for receiver type of amplifying active integrated microstrip monopole antenna for WLAN applications in IEEE 802.11b/g/a systems. The antenna will be fabricated on the FR4 microstrip board with er= 4.7 and tan0 = 0.019.The best value of the return loss at operation frequencies (ISM band) just will be less than -10 dB especially after intergrades the LNA to the antenna, and also the gain just will be greater than 10 dB and noise characteristics of the antenna will be enhanced(2~3dB).